2015
DOI: 10.3390/publications3010017
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent Citation of the Only Published Randomised Controlled Trial of Omega-3 Supplementation in Chronic Obstructive Pulmonary Disease Six Years after Its Retraction

Abstract: Scientific articles are retracted infrequently, yet have the potential to influence the scientific literature for years. The only randomised controlled trial to explore the effects of omega-3 polyunsaturated fatty acids in people with chronic obstructive pulmonary disease was retracted in 2008 due to falsified data. The objective of this research was to determine the frequency and nature of citations of this retracted paper. Web of Science and Google Scholar were used to determine the number of times the retra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…To conclude, in line with what earlier authors have found [ 16 18 , 26 ], propagation of retracted results through directly citing articles is a real scenario. On the other hand, in our case study, we have not seen propagation of a retracted result beyond those directly citing articles.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To conclude, in line with what earlier authors have found [ 16 18 , 26 ], propagation of retracted results through directly citing articles is a real scenario. On the other hand, in our case study, we have not seen propagation of a retracted result beyond those directly citing articles.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, they did not find examples of their scenario. Fulton and co-workers, on the other hand, have studied a single case in detail but have concentrated only on articles that directly cite the retracted article [ 26 ]. Like that paper, we focus on a single case because that way we have the possibility to study the contents of the papers involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, print journals have also been duped, such as the NEJM and Nature by the Duke University saga [58] and the Lancet by Wakefield's paper on MMR and Autism [59].Thus, both OA and non-OA journals have been victims of academic fraud. However, neither have responded appropriately, as revealed by low retraction rates (0.004%) and slow retraction times (three years) [60]; furthermore incomplete retraction databases allow high rates of post-retraction citation [61]. Considering this evidence neither OA nor subscription journals could claim to be of a higher standard.…”
Section: Quality Of Informationmentioning
confidence: 99%
“…The authors requested the following corrections to their paper [1]. On page 19 in the results section, "20 were classified as containing specific data and 30 were classified as cited in passing" was replaced with "18 were classified as containing specific data and 32 were classified as cited in passing".…”
mentioning
confidence: 99%